Redeeming organisational soul. (January 2019) - Wray-Bliss, Edward
'Organisational soul' has been used in popular management texts to celebrate corporations that are governed through the values and beliefs of their leaders. Apart from Bell, Taylor and Driscoll in this journal, organisational soul has received little critical scrutiny or conceptual exploration. This article examines the concept through significant texts and traditions in the West's long religio-philosophical engagement with soul – including poststructuralist and Nietzschean thought, Classical Greek philosophy, Aurelius Augustine's first hermeneutics of the subject and key constitutive moral practices of Late Antiquity and Early Christianity. Through such sources, I argue that we can understand neoliberal corporations to have souls, that this soul can be regarded as imperialist, that it is constituted through ethical-moral discourse and that it is subject to being disciplined – as we have come to understand human souls to be – through processes of governmentality. As such, this article posits that it may yet be possible to redeem organisational soul.